Sytuacja edukacyjna małoletnich matek, wychowanek placówek opiekuńczo-wychowawczych. Perspektywa biograficzna - Skowrońska-Pućka, Agnieszka (Studia Edukacyjne, 2020)
One of the most severe consequences resulting from premature motherhood is the inability or shortening of the education period. Author’s empirical verification indicate that the majority of researched girls (underage mothers, educational care facilities foster-children) quickly leave school and interrupt education once their child is born. The narration analysis indicated that its main cause was the difficulty in combining the role of a mother and a student, together with the lack of support from the closest. Only few girls managed to continue education, unfortunately they chose private, evening schools which are known for low quality education. The presented fragmentary empirical verifications indicate that early parenthood reduces the education period. Educational-care facilities foster-children, coming from low-educated families and professional qualifications find it particularly hard or impossible to achieve secondary or even lower-secondary education. Lack of education and professional qualifications has lead them to take up low-income jobs, that do not require any qualifications or to obtain money illegally. Recognizing various consequences of premature motherhood, both individual and social, there is no doubt that teenage mothers, especially foster children of educational-care facilities, should be taken care of. There is only one legal record concerning the education of pregnant student or underage mothers, however, it is not precise, which means that schools have to interpret it by themselves and introduce their own procedures. The subject of the present article is prevention, support and help given to underage pregnant students or underage mothers by the teachers, educators, or peers, who are potential beneficiaries of help, i.e. underage mothers fulfilling the education duty.